PENGARUH LINGKUNGAN KERJA FISIK DAN KESELAMATAN KERJA TERHADAP KEPUASAN KERJA PADA KARYAWAN BAGIAN PRODUKSI LOUFIE COLLECTION KABUPATEN TASIKMALAYA - Sindi Tonia; Mochamad Vrans Romi (JURNAL LENTERA BISNIS, 2025)
The physical work environment is a place where employees carry out activities every day. It is important to pay attention to a conducive work environment that provides a sense of security and allows employees to work optimally. Collection Tasikmalaya Regency accidents still often occur on average due to job characteristic factors, such as lack of knowledge and ability, workers who do not care about using personal protective equipment which in the end will become the potential for work accidents. This research aims to determine the influence of the physical work environment and work safety on job satisfaction among employees in the Loufie Collection Production section, Tasikmalaya Regency. The sampling technique uses a simple random sampling method. The data analysis used in this research used multiple linear regression analysis with the SPSS version 25.0 program. The respondents in this research were 33 employees of the Loufie Collection Production section, Tasikmalaya Regency. The results of this research show that both the physical work environment and work safety have a significant partial or simultaneous effect on job satisfaction among employees in the Loufie Collection Production Department, Tasikmalaya Regency.